RANCANG BANGUN APLIKASI ORDER MANAGEMENT SYSTEM (Information Technology and Telematics, 2014)
Abstract E-commerce is one of facilities for the sellers to promote their products by using the internet. E-commerce has been used by many sellers because it is cheap and its is able to be accessed everytime and everywhere by the buyers. Order Management System (OMS) is a shape of e-commerce which has some functions. OMS manages every activities : product promotion, payment activities, payment confirmation, product return, until product delivery system to the customer in good condition. Framework is a suitable method to implementice e-commerce OMS by using MVC(Model View Controller). Codeigniter is chosen because it provides a view class and library which has advantages in developing website V-castro Apparel. The result of this application is e-commerce website which has a function to control or manage every selling-buying activities and to make easy for V-castro Apparel in managing order. Keywords: E-commerce, Order Management System (OMS), Framework, Codeigniter.